2018
DOI: 10.1111/inr.12468
|View full text |Cite
|
Sign up to set email alerts
|

Social support for elderly people over 65 years in Spain

Abstract: These data suggest that it is necessary for nurses to know about the needs of older people to implement societal measures of health promotion, prevention and education that favour social cohort. In addition, health policymakers should establish programmes that improve the social support of non-institutionalized older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
0
9
0
5
Order By: Relevance
“…Support from children and participation in social activities had significant effects on the health of the elderly [34]. In addition, a large number of studies have shown that age, gender, and marital status are important demographic factors that affect the health of the elderly [35][36][37][38]. Socioeconomic status, such as income and education, also has a positive impact on the health of the elderly [39][40][41].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Support from children and participation in social activities had significant effects on the health of the elderly [34]. In addition, a large number of studies have shown that age, gender, and marital status are important demographic factors that affect the health of the elderly [35][36][37][38]. Socioeconomic status, such as income and education, also has a positive impact on the health of the elderly [39][40][41].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Em relação à mensuração do apoio social, escores inferiores foram veri cados em estudos nacional (74,43) (27) e internacional (70,22) (28) desenvolvidos entre idosos da comunidade. Os pro ssionais de saúde, em especial os enfermeiros, durante o cuidado prestado aos idosos, devem considerar de forma integral as questões que interferem na saúde, dentre elas o apoio social, que é tido como um fator de proteção para as boas condições de saúde dessa população (5,29) . Sendo assim, abordagens que fortaleçam o apoio social e possibilitam integrar a família e componentes da rede social à assistência, são recursos que podem ser apreciados e utilizados, por agregar qualidade à saúde desses indivíduos (26) .…”
Section: Discussionunclassified
“…Estes dados sugerem a necessidade dos pro ssionais de saúde, em especial os enfermeiros, conhecerem sobre as necessidades dos idosos para implementar medidas sociais de promoção da saúde e prevenção de agravos. Além disso, os formuladores de políticas de públicas devem estabelecer programas que estimulem e favoreçam o apoio social dos idosos da comunidade (29) .…”
Section: Discussionunclassified
“…For example ( Tab. II ), some aspects that are common to every area distinguish subjects mainly on the basis of their need for social and practical support, and thus, the family structure that may help or hinder prevention or care patterns and the implementation of a healthy lifestyle [ 15-17 ]. Other characteristics, such as educational level and/or housing conditions, display a differential impact on stratification by socio-economic conditions from area to area (i.e., they express more or less variance) according to the specific situation of the labor market, of the housing market etc.…”
Section: Discussionmentioning
confidence: 99%